INFLUENCE OF EXO- AND ENDOGENOUS FACTORS ON THE MORPHOLOGICAL AND FUNCTIONAL STATE OF THE SPLEEN AS AN IMPORTANT MEDICAL AND SOCIAL PROBLEM OF THE HEALTH CARE SYSTEM - O.V. Mamai; S.M. Bilash; R.M. Grinko (Проблеми екології та медицини)
Over the past century, since the rapid development of mankind as a civilization, the state of the environment and the conditions of everyday human existence have undergone significant changes. Diseases of the spleen play an important role in the system of pathologies of the human internal organs. The spleen is often considered a “forgotten organ” among clinicians and radiologists. Nevertheless, the spleen can be involved in a variety of congenital and acquired diseases, which makes it important to study the influence of exogenous and endogenous factors on its morphological and functional state. The aim is to analyze the literature data of modern studies published in the scientific and metric databases Scopus, Web of Science, and Google Scholar in English and Ukrainian and to summarize the results to identify key gaps in the known data. We found that the spleen’s functions are focused on systemic circulation, so it has no afferent lymphatic vessels. Spleen architectural features have been described in aging, chronic stress, sleep deprivation, under the influence of electromagnetic radiation, radiation exposure, sodium glutamate, sodium nitrite, and sodium fluoride. In forensic practice, trauma is considered the most common pathology of the spleen. Changes in the spleen are also known to occur in the setting of death from anaphylaxis, drowning, and sepsis. Autopsy of the spleen plays an important role in toxicological research. In clinical practice, spleen diseases are usually considered in the structure of other disease syndromes, but the main clinical changes are considered to be asplenia, splenomegaly, and hypersplenism. Thus, modern literature sources indicate a significant role of the spleen not only in the processes of immune regulation but also in maintaining the body’s homeostasis through participation in hematopoiesis and the body’s response to stress. At the same time, numerous studies have been conducted that indicate the vulnerability of the spleen to exogenous and endogenous factors, which is manifested by asplenia, splenomegaly, and hypersplenism. In particular, sodium glutamate and sodium nitrite have a significant effect on the spleen, but no data on their combined effect, as well as on the effect of Ponceau 4R on the spleen, have been found, which indicates the relevance of studying the effect of sodium glutamate, sodium nitrite, and Ponceau 4R in combination.